NFκB1 Dichotomously Regulates Pro-Inflammatory and Antiviral Responses in Asthma - Mandy Menzel; Hamid Akbarshahi; Irma Mahmutovic Persson; Cecilia Andersson; Manoj Puthia; Lena Uller (Karger Publishers, 2021)
Asthma exacerbations are commonly triggered by rhinovirus infections. Viruses can activate the NFκB pathway resulting in airway inflammation and increased Th2 cytokine expression. NFκB signaling is also involved in early activation of IFNβ, which is a central mediator of antiviral responses to rhinovirus infection. Using a mouse model, this study tests our hypothesis that NFκB signaling is involved in impaired IFNβ production at viral-induced asthma exacerbations. C57BL/6 wild-type and NFκB1−/− mice were challenged with house dust mite for 3 weeks and were subsequently stimulated with the rhinoviral mimic poly(I:C). General lung inflammatory parameters and levels of the Th2 upstream cytokine IL-33 were measured after allergen challenge. At exacerbation, production of IFNβ and antiviral proteins as well as gene expression of pattern recognition receptors and IRF3/IRF7 was assessed. In the asthma exacerbation mouse model, lack of NFκB1 resulted in lower levels of IL-33 after allergen challenge alone and was associated with reduced eosinophilia. At exacerbation, mice deficient in NFκB1 exhibited enhanced expression of IFNβ and antiviral proteins. This was accompanied by increased IRF3/IRF7 expression and induction of pattern recognition receptor expression. In a human asthma dataset, a negative correlation between IRF3 and NFκB1 expression was observed. NFκB may impair antiviral responses at exacerbation, possibly by reducing expression of the transcription factors IRF3/IRF7. These findings suggest a therapeutic potential for targeting NFκB pathways at viral infection-induced exacerbations.